Life Skills Education for People with Disabilities at Blind Orphanage “Tuah Sakato” West Sumatra Indonesia - Jendriadi Jendriadi; Warlan Sukandar; Rona Rossa (Department of Special Education, 2018)
This research was done because there is still the wrong assumption in the society that it will be ashamed if one of the family members has suffered from a disability. Even, they do not ready to receive him. One of the disabilities cases is blind. It is indicated by not being able to see either totally or partially. The blind people are caused by the different background. Some suffer are congenital birth, this blindness occurred since they were born. Then, The others happened when they are still teenagers and even adults, which is caused by several factors such as illness, accident, style of reading, or blindness is an undetectable cause. This research tries to reveal the various life skills education provided by the administrators of Blind Orphanage Tuah Sakato in West Sumatera so that the cynical and apathetic impression on the blind disabled patients will be reduced or even lost by knowing the various life skills that they get during their education. Thus, there is no longer the assumption that people with blind disabilities are only used as a sacrifice for begging on the streets or just working as a masseur only. In addition, this research also tries to describe the impression of alumni after taking education at Blind Orphanage Tuah Sakato West Sumatra Indonesia. The method used in this research is qualitative descriptive with direct participation approach. The techniques used are observation, interview and participate in their daily activities. The results of this field research obtained a lot of information about life skills provided by the managers for their students. By providing many life skills, their students are ready to return to the community. There are many life skills that are providing there. They are; preparatory classes, massaging skills by recognizing the structure of the human body, the ability of foreign languages, the ability to cook, the ability to play music, memorize the Qoran and recitation of the Qoran with rhythm, the ability to make speeches and they also got the counseling guidance so that they can be optimistic to look for their future. From the interviews that the authors conducted to the alumni of Blind Orphanage Tuah Sakato who had completed his education there, the results obtained that 90 percent said they are very satisfied with life skills education that has been given by the managers of Blind Orphanage Tuah Sakato and they feel like getting a new family and they are also assisted to find work.